"All-in-one" in vitro selection of collagen-binding vascular endothelial growth factor. (April 2018) - Park, Shin-Hye; Uzawa, Takanori; Hattori, Fumiyuki; Ogino, Shuichi; Morimoto, Naoki; Tsuneda, Satoshi; Ito, Yoshihiro
Abstract: To enhance the therapeutic effect of growth factors, a powerful strategy is to direct their localization to damaged sites. To treat skin wounds and myocardial infarction, we selected vascular endothelial growth factor (VEGF) carrying binding affinity to collagen. A simple conjugation of a reported collagen-binding sequence and VEGF did not increase the collagen-binding affinity, indicating that the molecular interaction between the two proteins abolished collagen binding activity. Here, we present a new molecular evolution strategy, "all-in-one" in vitro selection, in which a collagen-binding VEGF (CB-VEGF) was directly identified from a random library consisting of random and VEGF sequences. As expected, the selected CB-VEGFs exhibited high binding affinity to collagen and maintained the same growth enhancement activity for endothelial cells as unmodified VEGF in solution. Furthermore, the selected CB-VEGF enhanced angiogenesis at skin wounds and infarcted myocardium. This study demonstrates that "all-in-one" in vitro selection is a novel strategy for the design of functional proteins for regenerative medicine.